Dinosaurs and dioramas : creating natural history exhibitions - Chicone, Sarah J. (Left Coast Press, 2013)
"Two experienced exhibit designers lead you through the complex process of design and installation of natural history exhibitions. The authors introduce the history and function of natural history museums and their importance in teaching visitors the basic principles of science. The book then offers you practical tricks and tips of the trade, to allow museums, aquaria, and zoos--large or small--to tell the story of nature and science. From overall concept to design, construction, and evaluation, the book carries you through the process step-by-step, with emphasis on the importance of collaboration and teamwork for a successful installation. A crucial addition to the bookshelf of anyone involved in exhibit design or natural history museums"--